A New Method of Enteroscopy–The Double-Balloon Method. (1st April 2003) - Yamamoto, Hironori; Sugano, Kentaro
Abstract : The diagnosis and treatment of diseases of the small intestine have been impeded by difficult technical challenges. Traditionally, endoscopic evaluation of this organ has required open laparotomy with the surgically assisted passage of the scope through the intestine. Nonsurgical endoscopic techniques have been developed, including push enteroscopy, passage of a scope over a guide-string, and a method that depends on peristalsis to advance the instrument, but each of these is subject to severe limitations. A novel procedure has been devised, whereby an endoscope and a soft flexible overtube, each of which has an inflatable balloon attached to its distal end, are employed together. The technique is described in detail in the present article. Double-balloon enteroscopy allows visualization of the entire small intestine, to and fro examination of an area of interest, and the taking of biopsy specimens in a manner that is safer, quicker and less painful than previous techniques. It constitutes an important advance in the diagnosis and management of bleeding and other small intestinal disorders.